A carga dos transtornos por uso de cocaína no estudo de carga global de doenças no Brasil, 2000-2017 - Rayce dos Santos Crepalde (2019)
Cocaine abusive use and addiction are a serious public health issue. It is estimated that 0,4% of the world population, between 15 and 64 years old, has made use of cocaine in 2016. Global data on illicit drug use indicates Brazil as one of the emerging nations where the use of stimulants, such as, cocaine, snorted or smoked, is increasing. This work aims to describe and analyse the data from the estimates of the Global Burden of Disease Study (GBD 2017) of cocaine use disorders in Brazil and its Federal Units (UF) between 2000 and 2017. Estimates of GBD 2017 were used: agestandardized prevalence rate (ASPR) of addiction, age-standardized mortality rate (ASMR), and age-standardized rate of life years lost due to death or disability [DALY = YLL (years of life lost for premature death) + YLD (years lived with disability)], by sex and age group. It has also investigated the ratio between observed versus expected DALY (O/E), based on the SocioDemographic Index (SDI). Statistic models were used to produce the estimates. For all the metrics, Uncertainty Intervals of 95% (II95%) were used. For estimates of mortality rate, the GBD 2017 study used an algorithm for the redistribution of garbage codes, where International Classification of Diseases (ICD-10) codes of accidental poisoning (X40-X44 and X49) were redistributed to disorders for illicit drug use. The main preposition of this algorithm is the dominance of some substance when considering the intermediate causes of death by accidental poisoning, applying the following order: opioids; cocaine; amphetamines, psychoactive, and psychedelic drugs in the same level of fatality; then alcohol, and, finally, marijuana. The results show that Brazil has the sixth highest rate of DALY (43.45 / 100 thousand in hab. II95%: 30,19 - 60,37) of cocaine use disorders worldwide, affecting mainly men and young adults. There were not substantial differences in the burden of these disorders among the UFs. Between 2000 and 2017, there was positive variation in prevalence in absolute numbers (53%), as well as positive variation in the Age-Standardised Prevalence Rate (ASPR), with the rate of dependence of disorders due to cocaine use 2.33 times higher among men than among women. There was a statistically significant increase in MR in all UFs, ranging from 85% in the Federal District to 211% in Rio Grande do Norte. States with higher SID presented the lowest rates in the DALY O / E and the opposite took place in the states with low SID. Mortality and burden attributed to cocaine use are considered to be avoidable. In this sense, the statistic significant increase of MR of the disorders caused by cocaine use and the high rate of DALY of these disorders reinforce the need of new strategies in the public policies to face drug use in Brazil.